2014
DOI: 10.1002/jcp.24529
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the PKR Nuclear Interactome Reveals Roles in Ribosome Biogenesis, mRNA Processing and Cell Division

Abstract: The double-strand RNA-dependent protein kinase, PKR, plays a central role in inflammatory/chronic stress-mediated pathologies such as cancer, diabetes, and neuro/muscular degenerative diseases. Although a significant amount of research has been conducted to elucidate the role of PKR signaling in the cytosol, only recently has attention been paid to the role of PKR in the nuclear compartment. Previously our group reported that phosphorylated forms of PKR are present in the nucleus of acute leukemic cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 51 publications
(82 reference statements)
0
49
0
Order By: Relevance
“…For example, substrates of pPKR might be enriched near the chromosome region and recruit PKR. A recent mass spectrometry analysis on PKR interactome revealed that pPKR interacts with proteins involved in chromatin modification and cell division, such as BUB3 and NPM1 (Blalock et al 2014). Alternatively, it is possible that there may be different classes of dsRNAs that are localized to the chromosome region during mitosis and tether PKR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, substrates of pPKR might be enriched near the chromosome region and recruit PKR. A recent mass spectrometry analysis on PKR interactome revealed that pPKR interacts with proteins involved in chromatin modification and cell division, such as BUB3 and NPM1 (Blalock et al 2014). Alternatively, it is possible that there may be different classes of dsRNAs that are localized to the chromosome region during mitosis and tether PKR.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was performed as described elsewhere (41)(42)(43). Briefly, gel slices were washed in 100 mM ammonium bicarbonate (pH 8) and 50% acetonitrile (ACN), until completely destained, and then were digested with sequencing-grade trypsin (Promega, Madison, WI, USA) at 37°C.…”
Section: Ms Analysismentioning
confidence: 99%
“…12 Although PKR is primarily found in the cytoplasm where it regulates translation, about 20% of PKR is nuclear where it has been shown to regulate RNA splicing, mRNA stability, and ribosome biogenesis and affect diseases including acute myeloid leukemia AML. 1618 …”
Section: Introductionmentioning
confidence: 99%